2019
DOI: 10.1111/exd.13923
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 signalling pathway is implicated in keloid pathogenesis by preliminary transcriptome and open chromatin analyses

Abstract: Keloids are wounding‐induced fibroproliferative human tumor‐like skin scars of complex genetic makeup and poorly defined pathogenesis. To reveal dynamic epigenetic and transcriptome changes of keloid fibroblasts, we performed RNA‐seq and ATAC‐seq analysis on an early passage keloid fibroblast cell strain and its paired normal control fibroblasts. This keloid strain produced keloid‐like scars in a plasma clot‐based skin equivalent humanized keloid animal model. RNA‐seq analysis reveals gene ontology terms inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 29 publications
(35 reference statements)
1
60
0
Order By: Relevance
“…Chen et al [52] revealed that tanshinone IIA can inhibit the expression of PCSK9 through increasing the level of FoxO3a in HepG2 cells. In this study, we use assay for (ATAC-seq) [24] to show that EGCG regulates chromatic accessibility open region and find some potential TFs in HepG2 cells. But it is not clear whether two TFs, HNF-1α and FoxO3 are involved in PCSK9 regulation by EGCG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [52] revealed that tanshinone IIA can inhibit the expression of PCSK9 through increasing the level of FoxO3a in HepG2 cells. In this study, we use assay for (ATAC-seq) [24] to show that EGCG regulates chromatic accessibility open region and find some potential TFs in HepG2 cells. But it is not clear whether two TFs, HNF-1α and FoxO3 are involved in PCSK9 regulation by EGCG.…”
Section: Discussionmentioning
confidence: 99%
“…Assay for transposase-accessible chromatic with highthroughput sequencing (ATAC-seq) is a new technology for screening transcription factors [24]. This technology was performed by Annoroad Gene Technology, the protocol as following.…”
Section: Atac-seq and Analysis In Cellsmentioning
confidence: 99%
“…TLR3 expression on keratinocytes and activation of the downstream IL-6/STAT3 pathway is necessary for WIHN to occur, possibly through the promotion of transcription of Wnt/β-catenin signaling and Shh/Gli2 signaling [103]. In contrast, prolonged activation of IL6/STA3 in fibroblasts leads to fibrosis [104] and aggravated scarring such as keloids [105]. It is therefore tempting to speculate that TLR3/IL-6/STAT3, one of the damage-associated molecular pattern (DAMP) pathways, acts upstream of Wnt/β-catenin activity (Figure 1).…”
Section: Wound-induced Hair Follicle Neogenesis (Wihn)mentioning
confidence: 99%
“…Not surprisingly, research on skin morphogenesis benefits from many classic as well as newly emerging experimental approaches. Genomic approaches, including single‐cell profiling, are becoming especially powerful new research tools, exemplified by the use of RNA‐sequencing in several papers in this issue . Intravital imaging provides a platform to observe cellular behaviours in real time .…”
Section: Systems Biology Approach To Studying Skin Morphogenesismentioning
confidence: 99%
“…The review article by Chuong et al discusses the emerging evidence that in addition to molecular signals, regenerative responses in skin wounds are also profoundly controlled by mechanical cues. Two research papers examine the aspects of wound repair with high clinical relevance—regeneration of epidermal rete ridges in a Lanyu pig model and keloid scar formation in a humanized keloid fibroblast mouse model . Another study by Gurtner et al reports on age‐related changes to endogenous oxidative stress levels in mouse skin and how these changes affect myofibroblast differentiation and skin repair after wounding …”
Section: Skin Morphogenesis Across the Regenerative Levelmentioning
confidence: 99%